2009
DOI: 10.1007/s10646-009-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional responses to environmental metal exposure in wild yellow perch (Perca flavescens) collected in lakes with differing environmental metal concentrations (Cd, Cu, Ni)

Abstract: To investigate the mechanisms involved in metal stress in wild fish, yellow perch (Perca flavescens) were collected in eight lakes of the Rouyn-Noranda and Sudbury regions (Canada). Due to mining and smelting activities, these two regions indeed present a broad contamination gradient in metal concentrations (Cd, Cu, Zn and Ni; water, sediment and prey) and offer a unique research opportunity to investigate relationships between metal bioaccumulation and resulting deleterious effects in indigenous biota chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 41 publications
7
35
1
Order By: Relevance
“…This may be due to a decrease of oxygen availability in gills and then of ETS activity producing ATP, or could be due to a direct impact of Cu. Finally, results of the present study are in agreement with Pierron et al 12 They observed an increase in gene expression of CCOX subunit 1 and a decrease of CCOX enzymatic activity in wild yellow perch (Perca flavescens) in response to Cu exposure in lakes. Moreover a decrease of citrate synthase enzymatic activity has been shown in wild yellow perch muscle.…”
Section: Resultssupporting
confidence: 93%
“…This may be due to a decrease of oxygen availability in gills and then of ETS activity producing ATP, or could be due to a direct impact of Cu. Finally, results of the present study are in agreement with Pierron et al 12 They observed an increase in gene expression of CCOX subunit 1 and a decrease of CCOX enzymatic activity in wild yellow perch (Perca flavescens) in response to Cu exposure in lakes. Moreover a decrease of citrate synthase enzymatic activity has been shown in wild yellow perch muscle.…”
Section: Resultssupporting
confidence: 93%
“…For example, for ATP synthase, genes encoding for membrane subunits (c and f) were up-regulated while genes encoding for subunits located in the matrix (b and c) were down-regulated (Table 1, Tables S2, S3). As previously described in yellow perch liver (Pierron et al 2009), such an increase in the transcription levels of genes encoding for membrane subunits could reflect a compensatory mechanism to counteract the toxic effects of Cd and Cu on the mitochondrial inner membrane (Garceau et al 2010;Pierron et al 2009). Furthermore, the mitochondrial inner Fig.…”
Section: Energy Metabolismmentioning
confidence: 67%
“…For example, this could explain why increasing Cd concentrations were associated with a decrease in the transcription level of the gene encoding for acetyl-coenzyme A synthetase, a gene that is known to be up-regulated in response to PPAR activation by dietary fatty acids (Schoonjans et al 1995). In addition, previous studies have reported that in situ metal exposure impairs aerobic capacities of metal-contaminated yellow perch (Couture and Kumar 2003;Garceau et al 2010;Pierron et al 2009). Since lipids are the main fuel of aerobic ATP production, a Cd-induced impairment in lipid metabolism may be involved in the lower aerobic capacities reported in contaminated wild fish.…”
Section: Energy Metabolismmentioning
confidence: 98%
See 2 more Smart Citations